Fungsi Retoris Istifham dalam Surah Al-Mulk: Analisis Balaghah pada Ayat-Ayat Terpilih - Pandi Hakimi; Misnawati Misnawati (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2026)
Istifham is one of the rhetorical styles (uslub balaghah) frequently employed in the Qur`an. Its use does not always indicate a genuine question; rather, it often serves rhetorical purposes such as affirmation, reproach, warning, and denial. This study aims to analyze the forms of adawat al-istifham (interrogative particles) and their rhetorical functions in Surah Al-Mulk. This research employs a qualitative approach using the library research method. The primary data consist of verses containing istifham in Surah Al-Mulk, while the secondary data are derived from classical and contemporary Qur`anic exegeses, books on Arabic rhetoric (balaghah), and relevant scholarly literature. The analysis was conducted through the identification of adawat al-istifham, examination of Qur`anic interpretations, and rhetorical analysis based on the context of each verse. The findings reveal five forms of adawat al-istifham in the selected verses of Surah Al-Mulk, namely hal, alam, hamzah, awalam, and man. These interrogative particles perform four rhetorical functions: taqriri (affirmation) in verses 3 and 19, taubikhi (reproach) in verse 8, tahdidi (warning or threat) in verse 16, and inkari (denial) in verse 30. The study demonstrates that istifham in Surah Al-Mulk is not employed as a genuine inquiry seeking information, but rather as a rhetorical device that reinforces the messages of monotheism, warning, and reflection upon Allah’s power. Therefore, the meaning and function of istifham in the Qur`an are highly influenced by the context of the verse and the communicative purpose intended.